Socio-religious movement in the muslim society of Bengal during the British colonial period: Roles of Titumir (1782-1831) - S. M., Mostafizur Rahman (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.